STD, HPV and equity in public attention, continuing - Passos, Mauro Romero Leal (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Some people believe that everything is written in fate. Others strive for a fate. Here, we will argue supporting people who suffer from diseases that, besides causing serious physical problems, are linked to outstanding millennial prejudices.[...]